Digital Money and Central Bank Operations - Kahn, Charles; Alwazir, Jihad; Singh, Manmohan (Washington, D.C. : International Monetary Fund, 2022)
The rise of new and proposed monetary vehicles, including CBDC, stablecoins, payment service providers et cetera, are unprecedented. An important question for central banks is the extent to which these innovations upend the role of and implementation of monetary policy. The paper focuses on the interest rate channel and if digital money (especially CBDC) will change monetary policy and central bank operations. We argue that new policy instruments make sense only to the extent that there is limited substitutability between the various payment sectors. We analyze trends in currency-in-circulation, and how it may impact central bank's seigniorage, monetary base, and transactional velocity of digital money if money demand declines. Liquidity outside the monetary base will also be important to understand.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Base Money; Demand for Money; International Finance; International Financial Markets; Monetary Policy, Central Banking, and the Supply of Money